Basics of Human Resource Management - Kumar Tiwari , Anoop (Basics of Human Resource Management, 2022)
Engineering education primarily deals with technology, machines, projects and implementation. It focuses the instrumentation of a task to be engineered compiles into a plan and design in a shape of project. It primarily and largely focuses on tools and techniques, machines and measurements but at the same time ignores the human element involved in it. The present book makes a titular observation on the nature, focus and orientation of different kind of industries and their typical requirement of human resource. The book aims to enable the readers with an introductory approach towards the human resource, its recruitment, deployment and utility with object oriented management. The study of this book will enable the engineering graduates on special to find their status and suitability with different types of industries based on different requirement of human resource. At the same time this book targets to provide a fresh opinion about human resource management at the time industry 4.0.